Operasional Pembiayaan Usaha Syariah di PT. BPRS Kota Mojokerto sebagai Upaya Mempertahankan Non Performing Financing (NPF) 0% - Sanusi Anwar (Maliyah : Jurnal Hukum Bisnis Islam, 2019)
This study seeks to analyze Sharia Business Financing Operations (PUSYAR) as an effort to maintain 0% Non-Performing Financing (NPF) at PT. BPRS Mojokerto by taking a case study of the synergy of PT. BPRS Mojokerto, Baznas, Diskoperindag and Sharia Economic Community of Mojokerto, in the period 2012 to 2016. The research methodology used is a qualitative approach using qualitative descriptive analysis techniques. Data collection was carried out by means of field observations, interviews and documentation. Sharia Business Financing Program (PUSYAR) at PT. BPRS Mojokerto has succeeded in channeling financing to UKM and IKM in Mojokerto City from 2012 to 2016, and has succeeded in carrying out its function of channeling financing very well so that there has been no problem financing, and can maintain non-performing financing at zero percent (0%). The role of the parties involved greatly influences the success of the program. The findings of this study indicate that financing monitoring contributes to the performance of UMKM, so that awareness arises from UKM to pay installments on time. Financing monitoring carried out by the Bank will contribute to the performance of the UKM business.